Integrating Cellular and Bioprocess Engineering in the Non-Conventional Yeast Yarrowia lipolytica for Biodiesel Production: A Review - Xie, Dongming (Frontiers in Bioengineering and Biotechnology, 2017)
As one of the major biofuels to replace fossil fuel, biodiesel has now attracted more and more attention due to its advantages in higher energy density and overall less greenhouse gas generation. Biodiesel (fatty acid alkyl esters) is produced by transesterification of microbial/microalgae oils, plant oils, or animal fats with chemical catalysts or lipase. Currently, plant oils or waste cooking oils/fats remain the major source for biodiesel production via enzymatic route, but the production capacity is limited either by the uncertain supplement of plant oils or by the low or inconsistent quality of waste oils/fats. In the past decades, significant progresses have been made on synthesis of microalgae oils directly from CO2 via a photosynthesis process, but the production cost from any current technologies is still too high to be commercialized due to microalgae’s slow growth rate on CO2, inefficiency in photo-bioreactors, lack of efficient contamination control methods, and high cost in downstream recovery. At the same time, many oleaginous microorganisms have been studied to produce lipids via the fatty acid synthesis pathway under aerobic fermentation conditions, among them one of the most studied is the nonconventional yeast, Yarrowia lipolytica, which is capable of producing lipids at very high titer, rate, and yield from various economical substrates. This review summarizes the recent research progresses in both cellular and bioprocess engineering in Yarrowia lipolytica to produce lipids at a low cost that may lead to commercial-scale biodiesel production. Specific technologies include the strain engineering for using various substrates, metabolic engineering in high-yield lipid synthesis, cell morphology study for efficient substrate uptake and product formation, free fatty acid formation and secretion for improved downstream recovery, and fermentation engineering for higher productivities and less operating cost. To further improve the economics of the microbial oil-based biodiesel, production of lipid-related or -derived high-value products are also discussed.